A Study on SWOT Analysis of Pharmaceutical Industry: The Bangladesh Context - Hoq, Meem Rafiul; Ahsan, Md. Ali; Tabassum, Tanim–A (Global Disclosure of Economics and Business, 2013)
Pharmaceutical industry is one of the most important sector in Bangladesh. It is the only industry, which has its own strong manufacturing capabilities to produce the pharmaceuticals product. In this study it is tried to find out what types of strengths, weaknesses, opportunities and threats the pharmaceuticals companies face in Bangladesh. There are about 250 pharmaceuticals firms in Bangladesh. Among them some companies are the large size and more sophisticated. Some companies are small sizes and traditional qualities. A few companies dominate the whole medicine market. So they have to face severe competition in pharmaceuticals market. SOWT (Strength, Opportunity, Weakness, and Threat) analysis of any industry sector investigates the important factors that are possibility of the industry and influencing the companies operating in that sector. The purpose of this study is to analyze the pharmaceutical sector of Bangladesh using the framework of SWOT. This paper brings to light on the SWOT analysis of pharmaceuticals industry in Bangladesh and provided some valuables suggestions to overcome the weaknesses and threats, there are some suggestions to utilize the strengths and opportunities properly. Through this study the researchers try to discuss the affect of various macro-economic factors of strength, opportunity, weakness, and threat aspect on the industry and its related problems and prospects for the future. JEL Classification Code: O25; O25